Eco-environmental constraints, economic incentives, and spatiotemporal variations of construction land use efficiency in regional China - Wu, Jiawei; Liu, Chonggang; Sun, Wei (Frontiers in Ecology and Evolution, 2022)
Construction land expansion and use efficiency are tied to the promotion of sustainable cities and communities. This article explores how and why the spatiotemporal variation of construction land use efficiency (CLUE) evolved in the Yangtze River Delta (YRD), China between 2000 and 2020. Our descriptive results show that county-level regions with higher CLUE are concentrated in major cities in the core YRD, as well as ecologically sensitive regions in the peripheral YRD. Although CLUE improvement in peripheral regions has been more remarkable since the early 2010s, the efficiency gap in construction land use between the core YRD (central cities) and the peripheral YRD (suburban counties) has doubled. The modeling results indicate the temporally and spatially heterogeneous impacts of various factors related to economic incentives and eco-environmental constraints on the uneven CLUE. Economic level and ecological sensitivity are positively associated with regional CLUE. The continuing growth of service industries and the spatial agglomeration of knowledge-intensive and foreign-invested firms are increasingly vital for CLUE improvement in the core YRD, while the prosperity of manufacturing industries is more important for the peripheral YRD. The “crowding out effect” of environmental pollution on CLUE could be proved in the peripheral rather than the core YRD. Our findings suggest that proper policies should be tailored to specific places to coordinate construction land use, economic growth, and eco-environmental sustainability.